Integer-to-Integer Wavelet Transform Based ECG Steganography for Securing Patient Confidential Information. (2016) - Liji, C.A.; Indiradevi, K.P.; Babu, K.K. Anish
Abstract: Today Point-Of-Care system is being intensively used for moderating the medical influx in medical centres, with the patient's information liaised over internet to remote servers, hosted inside the hospital. Risk of Information Security of the data transmitted over internet is the biggest concern. To overcome the challenges of security, ECG-Steganography technique using Integer-to-Integer wavelet transform is proposed. Spatial domain steganography is executed wherein lifting scheme based Integer-to-Integer wavelet transform is employed to conceal the patient information in LSB location. Further, the data is scrambled inside the ECG signal through scrambling matrix and shared key. The patient's ECG signals are collected from Powerlab-Labchart system and PhysioNet database. The patient's information and physiological parameters are hidden inside the ECG signal and therein watermarked ECG signal is produced. The PRD of original and Watermarked ECG signal is measured and a maximum value of 0.4% is obtained. Based on the result, it is observed that the hidden data is extracted perfectly.